Estimativas trimestrais das transferências públicas de assistência e previdência no Brasil no período 1995-2012 - Cláudio Hamilton M. dos Santos; Raphael Rocha Gouvea; Ésio Moreira Leal; Isabela D'loan Silva Le\~ao (Instituto de Pesquisa Econômica Aplicada (IPEA), 2014)
– It is difficult to exaggerate the macroeconomic and political relevance of the public transfers to the private sector in the Brazilian economy. These transfers have reached 15% of GPD in the last decade. However, there are just a few papers analyzing the evolution of these transfers. Given that, this paper has three main goals. First, to show how to construct an annual series compatible with the Brazilian national accounts system (ref. 2000) over the period 1995-2012. Second, to refine and extend (up until 2012) the previous effort of Santos, Macedo e Silva and Ribeiro (2010). Finally, we provide a short analysis of the numbers estimated for the aforementioned transfers.
Keywords: H53; H55; E01; 330; Brazilian government transfers to households; Brazilian quarterly national accounts; Brazilian social benefits other than social transfers in kind